2017
DOI: 10.1016/j.seizure.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between iron deficiency anemia and febrile seizures in children: A systematic review and meta-analysis

Abstract: The results of this meta-analysis suggest that IDA is associated with an increased risk of FS in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 39 publications
2
42
0
1
Order By: Relevance
“…Comparison of clinical and laboratory findings of patient and control groups showed that Hb, platelet counts, and blood sodium levels were significantly lower in the FS group than those in the FC and HC groups. It has been shown that iron deficiency anemia may be related to the increased risk of children suffering from FS and is one of the risk factors for FS (15). Similarly, studies have found that the reduction of peripheral blood platelet counts in children with FS may be related to the release of a large number of inflammatory mediators caused by platelet activation caused by infection (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of clinical and laboratory findings of patient and control groups showed that Hb, platelet counts, and blood sodium levels were significantly lower in the FS group than those in the FC and HC groups. It has been shown that iron deficiency anemia may be related to the increased risk of children suffering from FS and is one of the risk factors for FS (15). Similarly, studies have found that the reduction of peripheral blood platelet counts in children with FS may be related to the release of a large number of inflammatory mediators caused by platelet activation caused by infection (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Following these conflicting results, four recent meta-analyses indicated that iron deficiency anemia significantly increased the risk of febrile seizures with an OR of 1.27–3.78 [25–28]. In the meta-analysis by Kwak et al [32], iron deficiency anemia, diagnosed based on plasma ferritin (OR 3.78; 95% CI, 1.80–7.94; P < 0.001) or MCV (OR 2.08; 95% CI, 1.36–3.17; P = 0.001), was associated with febrile seizures. Karimi et al [33] performed subgroup analyses of simple febrile seizures and first febrile seizures, and obtained an OR of 2.98 (95% CI, 1.67–5.31) and 2.23 (95% CI, 1.33–3.73), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…23,2 Iron deficiency anaemia may predispose to febrile seizures. 22,[24][25][26][27][28][29][30] Studies have also shown that the stress from fever or seizure results in leucocytosis with neutrophilic predominance following release of epinephrine. 31 Recurrence of seizure episodes and concern about epilepsy are major parental concerns regarding long term effects of febrile seizure.…”
mentioning
confidence: 99%